Surgical and Endoscopic Intervention for Chronic Pancreatitis in Children: The Kings College Hospital Experience - Renos M. Jeropoulos; Deepak Joshi; Bashar Aldeiri; Mark Davenport (MDPI AG, 2024)
Paediatric chronic pancreatitis (CP) is a rare and debilitating pathology that often requires invasive diagnostics and therapeutic interventions either to address a primary cause such as a pancreaticobiliary malunion or to deal with secondary complications such as chronic pain. Endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS) are two endoscopic modalities that have an established diagnostic role in paediatric CP, and their therapeutic utilisation is increasing in popularity. Surgical decompression of the obstructed and dilated pancreatic duct plays a role in alleviating pancreatic duct hypertension, a common association in CP. Surgery equally has a role in certain anatomical abnormalities of the pancreaticobiliary draining system, or occasionally in some CP complications such as drainage of a symptomatic pancreatic pseudocyst.